2016
DOI: 10.1097/01.aoa.0000479509.27742.bc
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Outcomes After Uterine Balloon Tamponade for Postpartum Hemorrhage

Abstract: P = 0.06), and were less likely to have emergency deliveries (P = 0.001) than the women treated before March 2011. There were no significant differences in neonatal outcomes or maternal postoperative stay between the 2 groups.The results of this study indicate that a standardized multidisciplinary management approach for patients suffering from a morbidly adherent placenta resulted in better maternal outcomes, especially in cases of increta and percreta where the placental invasion was more aggressive. This mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These results are encouraging and show the efficacy of the intra-uterine balloon in the management of IPPH. Several authors have reported results similar to ours [4,[6][7][8]. Indeed, in the Condous series of 16 patients with persistent bleeding, Sengstaken-Blakemore catheterization was effective in 14 of them, only 2 patients required a surgical procedure because of a placenta Praevia [7].…”
Section: Discussionsupporting
confidence: 74%
“…These results are encouraging and show the efficacy of the intra-uterine balloon in the management of IPPH. Several authors have reported results similar to ours [4,[6][7][8]. Indeed, in the Condous series of 16 patients with persistent bleeding, Sengstaken-Blakemore catheterization was effective in 14 of them, only 2 patients required a surgical procedure because of a placenta Praevia [7].…”
Section: Discussionsupporting
confidence: 74%
“…Hysterectomy to avoid maternal death should be performed ‘sooner rather than later’, according to the Royal College of Obstetricians & Gynaecologists (RCOG) . Intrauterine balloon tamponade, arterial embolization, arterial ligation and uterine compression sutures have all been reported to be effective in stopping hemorrhage and preventing hysterectomy . Yet, if unsuccessful, these interventions may also delay hysterectomy, especially because they are performed with low frequency, and thus, experience with these techniques may be insufficient.…”
Section: Improving Maternal Outcomes: Obstetric Interventions To Stopmentioning
confidence: 99%
“…Intrauterine balloon tamponade, arterial embolization, arterial ligation and uterine compression sutures have all been reported to be effective in stopping hemorrhage and preventing hysterectomy [40][41][42][43][44][45][46][47][48][49][50][51]. Yet, if unsuccessful, these interventions may also delay hysterectomy, especially because they are performed with low frequency, and thus, experience with these techniques may be insufficient.…”
Section: Improving Maternal Outcomes: Obstetric Interventions To Stopmentioning
confidence: 99%
“…The RCOG recommends balloon tamponade for uterine atony and placental site anomalies to reduce bleeding. Balloon tamponade is a safe, effective, and easy way to treat primary postpartum hemorrhage (Martin et al, 2015;No, 2016). Hysterectomy was 75% less likely with gauze uterine packing (Schmid et al, 2013).…”
Section: Introductionmentioning
confidence: 99%